MAŁŻEŃSTWO I RODZINA W ŚWIADOMOŚCI POLAKÓW – ANALIZA SOCJOLOGICZNA - Mariański, Janusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article primarily concerns the perception of marriage and family life among both young and adult Polish people. We focus on family consciousness or the pro-family ideology, recognized values and pro-family norms. The subjective and conscious dimension of marriage and family life is conditioned by a variety of references in the macro and microstructure. However, marriage and family life as such also affects the attitudes and behavior of people, especially family members. Our study shows that about 25% of young people in Poland approve of the values and norms of Catholic ethics of marriage and family; about 50% take a selective attitude, and about 25% have completely departed from Catholic morality. With regard to the entire Polish society, acceptance of these values and norms stands at about 40%; partial approval and partial disapproval (a selective attitude) – 40%, and total disapproval – 20%. The approval of the pro-family values and norms among practicing Catholics only, would come out to be, at least, 5% greater.